Pengaruh layanan kotak literasi cerdas terhadap minat baca masyarakat di Pangandaran - Kiasati, Almas Inti; Heriyanto, Heriyanto (Daluang: Journal of Library and Information Science, 2022)
Introduction. The level of public interest reading in West Java, especially in Pangandaran Regency is in the low category, this is due to the lack of facilities that support public interest reading. One of the efforts of West Java local government to increase the public interest reading is by distributing Kotak Literasi Cerdas services or Kolecer to several districts and cities in West Java, including in Pangandaran Regency. This study aims to analyze the effect of library services, namely Kotak Literasi Cerdas or Kolecer on public interest reading in Pangandaran Regency.Methodology. This research is a quantitative study that shows the effect of variable X (Kolecer service) to variable Y (public interest reading). The population in this study amounted to 500 people, with a sample of 50 respondents. The data was collected by distributing questionnaires and observation. Meanwhile, the data analysis technique used descriptive statistical analysis and intervention statistical analysis, namely correlational analysis and simple linear regression. Results and discussion. This study indicates that there is a moderate positive effect between Kolecer services and public interest reading, which is 25.2%. In addition, several facilities from Kotak Literasi Cerdas service get an average mean value of 4.28.Conclusion. Reading interest influenced by the accessibility to books and other reading maerials. One of the public services offered is Kotak Literasi Cerdas which has proven to help communities build their reading interest.